1999
DOI: 10.1093/emboj/18.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of JNK signaling by GSTp

Abstract: Studies of low basal Jun N-terminal kinase (JNK) activity in non-stressed cells led us to identify a JNK inhibitor that was purified and identified as glutathione S-transferase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
854
3
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,028 publications
(900 citation statements)
references
References 55 publications
(83 reference statements)
22
854
3
7
Order By: Relevance
“…GSTp was demonstrated to be directly associated with JNK [188] and its monomeric form was shown to inhibit JNK activation in a manner that was independent on MEKK1-MKK4, the physiological upstream activators of JNK. In response to an oxidant stress, GSTp oligomerizes, and dissociates from JNK1, promoting its activation [189] (Figure 2, box 4). Importantly, mouse embryo fibroblasts from GSTp-null mice exhibited a high basal level of JNK activity, [189] and GSTp-null mice showed a phenotype of increased myeloproliferation, in association with activation of JNK and the JAK/STAT pathway [190], corroborating the functional significance of GSTp in the regulation of JNK, and potential other pathways in vivo.…”
Section: Redox Control Through Functional Dimerization Of Redox Enzymmentioning
confidence: 99%
See 1 more Smart Citation
“…GSTp was demonstrated to be directly associated with JNK [188] and its monomeric form was shown to inhibit JNK activation in a manner that was independent on MEKK1-MKK4, the physiological upstream activators of JNK. In response to an oxidant stress, GSTp oligomerizes, and dissociates from JNK1, promoting its activation [189] (Figure 2, box 4). Importantly, mouse embryo fibroblasts from GSTp-null mice exhibited a high basal level of JNK activity, [189] and GSTp-null mice showed a phenotype of increased myeloproliferation, in association with activation of JNK and the JAK/STAT pathway [190], corroborating the functional significance of GSTp in the regulation of JNK, and potential other pathways in vivo.…”
Section: Redox Control Through Functional Dimerization Of Redox Enzymmentioning
confidence: 99%
“…In response to an oxidant stress, GSTp oligomerizes, and dissociates from JNK1, promoting its activation [189] (Figure 2, box 4). Importantly, mouse embryo fibroblasts from GSTp-null mice exhibited a high basal level of JNK activity, [189] and GSTp-null mice showed a phenotype of increased myeloproliferation, in association with activation of JNK and the JAK/STAT pathway [190], corroborating the functional significance of GSTp in the regulation of JNK, and potential other pathways in vivo. GSTp also is an important regulator of peroxiredoxin 6 (1-cysPrx), via a mechanism that involves heterodimerization of the oxidized catalytic cysteine of 1-cysPrx with pi GST followed by its GSH-mediated reduction and enzyme activation [191].…”
Section: Redox Control Through Functional Dimerization Of Redox Enzymmentioning
confidence: 99%
“…When oxidized by formation of a disulfide between the two cysteines in its active site, Trx dissociates from ASK1, allowing it to become activated (46)(47)(48)(49)(50)(51)(52)(53) (Figure 1). Also, GSTΠ inhibits c-Jun-N-terminal kinase (JNK) but dissociates and allows JNK activation when its critical active site cysteine is oxidized (54)(55)(56). The bacterial transcription factor, OxyR (57) and the eukaryotic transcription factors AP-1 (58) and NF-κB (59) also contain critical cysteine residues that are targets of signaling.…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 99%
“…Recently, Adler and co-workers have reported that GSTP1 can act to alter intracellular signaling through an interaction with Jun N-terminal kinase (JNK). 41 Decreased GSTP1 expression might therefore alter intracellular signaling and this effect would provide a plausible biochemical mechanism to explain a role in prostate carcinogenesis. The description of the effect of TER 199, a highly specific GSTP1 inhibitor, in stimulating growth of granulocytes further suggests a potentially important regulatory role for the GSTP1 protein.…”
Section: Discussionmentioning
confidence: 99%